Engagement académico y éxito escolar: análisis desde el Utrecht Work Engagement Scale for Students (UWES-S): Academic engagement and school success: analysis from the Utrecht Work Engagement Scale for Students (UWES-S) - Nunura Reyes, Gissella Ivonne; Muniz Pin, Guadalupe Gisella; Ponce González, Lorena Magdalena; Nunura Reyes, Jesus Eugenia; Manrique Toala, Grover Virgilio (LATAM Revista Latinoamericana de Ciencias Sociales y Humanidades, 2025)
The present study aimed to analyze academic engagement as a predictor of academic performance in elementary and high school students from three educational institutions in the city of Jipijapa. The sample consisted of 81 students between the ages of 8 and 19, who were administered a questionnaire adapted from the Utrecht Work Engagement Scale for Students (UWES-S), which measures the dimensions of vigor, dedication, and absorption using a Likert-type scale. The results showed a moderate level of academic engagement with a positive trend, highlighting higher scores in general satisfaction with classes (M = 3.8; SD = 1.2) and enthusiasm for the learning topics (M = 3.6; SD = 1.1), while adaptation to the teaching method obtained the lowest values (M = 3.1; SD = 1.3). The analysis of the distributions showed that the majority of students fell into the upper categories of the scale, reflecting a positive assessment of their academic experience, although with variability in concentration and adaptability. In conclusion, the findings indicate that, despite the presence of a group of students with lower motivation, the general trend points to favorable academic engagement, which can be considered a protective factor against academic burnout. This highlights the need to implement pedagogical strategies that strengthen motivation, enhance concentration, and contribute to improving the quality of the teaching-learning process.